Lean six sigma methodology to reduce excess wastage in a brickyard: a case study - Quiroz-Flores, Juan Carlos (2023)
Peruvian companies’ craft brick stands currently experience significant growth in sales. Thus brickyards seek to reduce the amount of waste to increase productivity and reduce cost overruns. In this study, the problem that has the greatest economic impact on a brick company is the excessive amount of waste. For this reason, the implementation of a model based on the Lean Six Sigma (LSS) methodology is proposed, applying Poka Yoke, Jidoka, Standardised Work, and Just in Time in order to reduce the number of defective bricks and cost overruns. The research project focused on the tambourine brick, the type whose percentage of generated waste is the highest in the production batch. To do this, the current situation was analysed; the main causes of the problem were identified and measured; and then Lean Six Sigma tools were used to attack the root cause. Finally, the proposed design reduced overheated bricks by 2.36%, wet bricks by 2.01%, and poorly stacked bricks by 1.8%, obtaining a 6.92% reduction in shrinkage and increasing the level of Six Sigma to 3.9, which contributed to the reduction of losses in the brickyard.